2015
DOI: 10.1530/erc-14-0490
|View full text |Cite
|
Sign up to set email alerts
|

Highly specific role of the insulin receptor in breast cancer progression

Abstract: Accumulating evidence from clinical trials indicates that specific targeting of the IGF1 receptor (IGF1R) is not efficient as an anti-breast cancer treatment. One possible reason is that the mitogenic signals from the insulin receptor (IR) can be processed independently or as compensation to inhibition of the IGF1R. In this study, we highlight the role of the IR in mediating breast tumor progression in both WT mice and a hyperinsulinemic MKR mouse model by induction of Ir (Insr) or Igf1r knockdown (KD) in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(50 citation statements)
references
References 46 publications
2
48
0
Order By: Relevance
“…Taken together, it suggests a significant role for changing expression levels of the different PI phosphorylation species in the dysregulation of normal cell-cell contacts, cell polarization, signal transduction, and membrane trafficking events [4,6,7,33,34]. While it is understood that many factors play a role in this T2D-cancer nexus (e.g., pharmaceutical treatments [9,13,33,35], hyperinsulinemia [3,12], and inflammation [5,[36][37][38][39]), there is significant evidence that increased glucose metabolism, and therefore a hyperglycemic microenvironment, is fundamental in the development of cancer [12,40]. Hence, we endeavored to determine the T2D glycemic effects on the cancerous microenvironment by studying the related changes in the PI phosphorylation profile.…”
Section: Introductionmentioning
confidence: 93%
“…Taken together, it suggests a significant role for changing expression levels of the different PI phosphorylation species in the dysregulation of normal cell-cell contacts, cell polarization, signal transduction, and membrane trafficking events [4,6,7,33,34]. While it is understood that many factors play a role in this T2D-cancer nexus (e.g., pharmaceutical treatments [9,13,33,35], hyperinsulinemia [3,12], and inflammation [5,[36][37][38][39]), there is significant evidence that increased glucose metabolism, and therefore a hyperglycemic microenvironment, is fundamental in the development of cancer [12,40]. Hence, we endeavored to determine the T2D glycemic effects on the cancerous microenvironment by studying the related changes in the PI phosphorylation profile.…”
Section: Introductionmentioning
confidence: 93%
“…A better understanding of the IR role in cancer may have important implications considering that clinical trials indicate that inhibitors specifically targeting the IGF-1R are not efficient for inhibiting cancer [95,96] and one possible reason is that the mitogenic signal might be independently processed by the IR, even as compensation to the inhibition of the IGF-1R. Indeed, a recent experimental study has suggested a highly specific role of the IR in breast cancer progression [97].…”
Section: Insulin Receptors As Prognostic Markers In Cancermentioning
confidence: 99%
“…13,14). IR and IGF1/2R have essential roles in energy metabolism, cell growth, division, and differentiation (15)(16)(17), and various studies suggest that aberrant IR/IGF1/2R signaling drives tumorigenesis in breast, lung, hepatocellular, and pancreatic cancers (18)(19)(20)(21)(22). IGF1R has been shown to be overexpressed in wild-type and pediatric GIST (23,24) and is a potential therapeutic target in GIST lacking KIT and PDGFRA mutations (25).…”
Section: Introductionmentioning
confidence: 99%